Elastomeric high-κ composites of low dielectric loss tangent: Experiment and simulation. (15th November 2020) - Ko, Youngpyo; Yoon, Hyungsuk; Kwon, Seulki; Lee, Hyunjung; Park, Min; Jeon, Insu; Lim, Jung Ah; Chung, Seungjun; Lee, Sang-Soo; Sung, Bong June; Kim, Jong-Ho; Kim, Heesuk
Abstract: As practical interest in wearable electronic devices and biomimetic transducers increases, the demand for elastomers with excellent dielectric behavior as well as good mechanical properties is growing. Herein, we propose a new concept of carbon black (CB)-embedded polydimethylsiloxane (PDMS) composites with high dielectric properties via a one-pot process. The dispersant-grafted CB3wt% /PDMS composites show an enhanced dielectric constant of 1090 with low loss tangent as low as 0.45 at 100 Hz, which is 340- and 145-fold higher than those of the pure PDMS and dispersant-free CB3wt% /PDMS, respectively. Experimental and simulation studies demonstrate that the dielectric properties of CB/PDMS composites depend on the CB dispersion in the PDMS matrix, which is influenced by the chain length of dispersant and the amount of residual dispersant. As a proof of concept, the capacitive pressure sensor based on CB/PDMS flat structure has been demonstrated, exhibiting 46-fold larger capacitance change than the pure PDMS based sensor. These results indicate that the sensor sensitivity can be significantly improved without additional micro-structuring and the large capacitance change enhances a tolerance to external noise sources. We believe that the elastomers with high dielectric properties show great potential for electronic applications including capacitive pressure sensors that should respond to various input pressures.